SPECIES COMPOSITION OF CORN AGROCENOSIS MAIN PESTS OF THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Lyaska, Yu. M.; Strygun, О. О. (Scientific Progress & Innovations, 2019)
Corn pests are one of the main factors limiting the yield increase, because they are present on the crops throughout the whole vegetation period, and damage plants at all development stages – from seeds in the soil to grain during storage, so the knowledge of the species composition of harmful corn insects, the period of their appearance and the stage of harm will enable to use the most effective measures to control the number of phytophages, which will ensure optimal phyto-sanitary condition of the sown areas and minimize the use of pesticides. Corn is damaged by almost 200 insect species on the territory of Ukraine, but 20 species among them cause great economic losses in different zones. Plants damaged by pests, have reduced productivity, low quality seeds, bad food and feed quality. That is why the purpose of our research was to establish the species composition, their population, dominance and spreading of harmful corn insects in the conditions of the Left-Bank Forest-Steppe of Ukraine, to identify their harmfulness depending on abiotic and biotic factors. As a result of the research in 2017-2018, the analysis of phyto-sanitary condition of the corn field agrocenosis in the above mentioned zone was carried out. It was found that the greatest harm to corn seedlings was caused by larvae of eight species of tick beetles (Elateridae) and larvae of lamellar (Scarabaeidae). The most dangerous pests of corn generative organs in 2017-2018 were the corn worms (Helicoverpa armigera Hbn., Noctuidae family, Lepidoptera squad), populating corn crops up to 75 % with 67.5 corn worms per 100 plants. During the vegetation season, the following types of pests were present on plants: cereal flies (Chloropidae), Rhopalosiphum padi L. and wheat aphid (Schizaphis graminum Rond.), cereal striped flea (Phyllotreta vittula Redtenb), European corn borer (Ostrinia nubilalis Hbn.), bugs of the family (Miridae), tarnished plant bug (Lygus), the ground beetle (Zabrus tenebrioides Goeze.), Oulema lichenis Voet., leafhopper (Macrosteles laevis Rib.) and dark leafhopper (Laodelphax striatella Fall). The presence of these phytophages on corn crops did not exceed EPV. The dominating entomophages were: Coccinella septempunctata L., Adonia dipunctata L., thrips (Aeolothrips intermedius Bagn.), carabid beetles (Carabidae), Chrysoperla larnea St., and hover flies (Syrphidae).